Analysis of Summative Assessment and Influencing Factors of The Results on ‘Ilm Ṣarf Among Arabic Education Students at Universitas Muhammadiyah Yogyakarta - Nabawi, Widia; Nurdianto, Talqis; Madjid, Muh. Naim; bin Zakaria, Muhamad Zaidi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This study aims to analyze the summative assessment and influencing factors of the results on ‘ilm ṣarf among arabic education students at Universitas Muhammadiyah Yogyakarta. This study uses a mixed method, with a quantitative approach with statistical test analysis techniques (normality test, variance homogeneity test and t-independent test) as well as a qualitative approach through interviews and documentation. The research subjects consisted of 53 students from both classes. The results of the study showed that there was an average difference between the two classes, class A had an average score of 82.84 and class B 83.15. The applied statistical tests include normality test, variance homogeneity test and t independent samples test to determine the significance of the difference in values. Statistical analysis concluded that there was no significant difference between the average scores of the two classes. Factors that affect student learning outcomes include study preparation, interests, motivation, family support, methods, facilities and social environment. Family factors and interlocking methods are able to make a large contribution to the assessment results, while campus facilities and social environment have a smaller influence. This research provides insight into the dynamics of learning in ‘ilm ṣarf courses and the importance of paying attention to internal and external factors and the educational process.